1991
DOI: 10.1159/000168299
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characterization of Drug-Induced Allergic Nephritis

Abstract: To elucidate the clinical characterization of drug-induced allergic nephritis (DIAN), we analyzed the cases attending our department. We now report on the 14 cases of DIAN due to administration of penicillin in 2 cases, cephem antibiotics in 6 cases, nonsteroidal anti-inflammatory drugs in 4 cases and new quinolone anticidal drugs in 2 cases. With 1 exception, all these cases reached the stage of acute renal failure after taking these drugs for 2–13 days, followed by characteristic allergic symptoms such as fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…The creatinine clearance was 95.5 ml/min per 1.73 m 2 . A 67-gallium scintigram for tubulointerstitial nephritis [10] demonstrated an abnormal uptake in the kidneys. A percutaneous renal biopsy was performed on hospital day 4.…”
Section: Discussionmentioning
confidence: 99%
“…The creatinine clearance was 95.5 ml/min per 1.73 m 2 . A 67-gallium scintigram for tubulointerstitial nephritis [10] demonstrated an abnormal uptake in the kidneys. A percutaneous renal biopsy was performed on hospital day 4.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of hypercoagulable conditions is multifactorial with mechanisms including release of proteins by activated lymphocytes and eosinophils, and co-morbid predisposing factors such as bed rest. In the patient reported here, the significantly high concentration of ECPin the serum suggested that he had had a hypersensitivity reaction, possibly to PIPC, and that activated eosinophils might play a role in the pathogenesis of hypercoagulopathy and acute renal failure (8,16). Weconsider it unlikely that any causes other than the administration of PIPCwere responsible for the present reactions.…”
Section: Discussionmentioning
confidence: 54%
“…As the serumcreatinine concentration and urinalysis were normal 4 months prior to the onset of acute tubulointerstitial nephritis, and cefdinir was the only drug prescribed during the pre-onset period, cefdinir is the likely cause. Shibasaki et al have concluded that the drug lymphocyte stimulation test is applicable to the etiologic diagnosis of drug-induced acute tubulointerstitial nephritis, finding a sensitivity in identifying the suspected agent of 75% (9/12), while all drugs administered except for the suspected agents tested negative (9). Therefore, we concluded that cefdinir caused the acute tubulointerstitial nephritis in this case.…”
Section: Discussionmentioning
confidence: 54%